Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1021/jm00089a026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis by proton spin-echo NMR. 2. Oxidation of intracellular glutathione as a consequence of penicillamine therapy in rheumatoid arthritis

Abstract: Spin echo NMR analysis is used to monitor the effect of penicillamine on intact erythrocytes obtained from patients suffering from rheumatoid arthritis during a 12-week period of therapy. The results are compared to the previously reported in vitro effects of the compound (McKay, C. N. N.; et al. Biochim. Biophys. Acta 1986, 888, 30-35). At clinical assessment at week 12, the 20 patients were divided into responder and nonresponder groups. The intracellular glutathione in the responder group is more oxidized (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 5 publications
0
17
0
1
Order By: Relevance
“…It has been suggested that their beneficial action is due to their ability to scavenge oxygen radicals [20], thus reducing the stress on the cell and resulting in less oxidation of glutathione which is also a radical scavenger. However, in this study it was found that captopril and NAC produced opposite effects on the glutathione pool, with NAC causing a shift to a more reduced state and captopril producing a more oxidised glutathione pool, similar to the effect of penicillamine [3]. Exogenous glutathione, which has previously been reported to stimulate the reduction of intracellular glutathione in a manner similar to NAC [22,23], was found to have no effect on the endogenous glutathione.…”
Section: Discussionmentioning
confidence: 44%
See 4 more Smart Citations
“…It has been suggested that their beneficial action is due to their ability to scavenge oxygen radicals [20], thus reducing the stress on the cell and resulting in less oxidation of glutathione which is also a radical scavenger. However, in this study it was found that captopril and NAC produced opposite effects on the glutathione pool, with NAC causing a shift to a more reduced state and captopril producing a more oxidised glutathione pool, similar to the effect of penicillamine [3]. Exogenous glutathione, which has previously been reported to stimulate the reduction of intracellular glutathione in a manner similar to NAC [22,23], was found to have no effect on the endogenous glutathione.…”
Section: Discussionmentioning
confidence: 44%
“…Oxidative stress is a facet of many disease processes such as chronic heart failure [1,2], rheumatoid arthritis [3] and Graves disease [4], and it has recently been implicated in AIDS [5,6]. Chronic heart failure is further complicated by reperfusion injury, where the rapid introduction of oxygen into the ischaemic region generates active oxidants and increases tissue damage [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations